Effect and Remediation of Environmental Pollution on the Concept of Chemistry - Review - Abubakar, Musa Yahaya; Haladu, Mohammed; Titilayo, Ogunwole Adeshewa; Adam, Ansar Bilyamin (Darul Yasin Al Sys, 2024)
The science of chemistry has been greatly impacted by environmental degradation, which has led to important breakthroughs and changed educational perspectives. This review highlights the role of chemists in tackling global environmental concerns by examining the diverse effects of environmental contamination on the study of chemistry. Green chemistry principles, which attempt to design safer chemicals and processes that limit waste and lessen detrimental environmental impacts, have been motivated by pollution. Environmental chemistry, which focuses on the behavior, consequences, and mitigation of pollutants, has emerged as a crucial sub-discipline as a result of the pressing need to address pollution. In addition, pollution has made it necessary to integrate interdisciplinary techniques, bringing together the fields of chemistry, biology, environmental science, and engineering to provide novel ways to pollution treatment and control. Educational curricula have evolved to incorporate these trends, emphasizing sustainable practices and the environmental implications of chemical processes. This review highlights how the growing awareness of environmental pollution continues to drive innovation and shape the future of chemical education and research, underscoring the importance of chemists in developing sustainable solutions to protect our planet.